Evaluating Bunkers' storm motion of hail-producing supercells and their storm-relative helicity in Germany - Mathis Tonn; Jannik Wilhelm; Michael Kunz (Meteorologische Zeitschrift, 2023)
This paper presents a statistical analysis of the motion of hail-producing supercells in Germany based on data from a radar-based cell detection and tracking algorithm and a mesocyclone detection algorithm. The parameterization of supercell motion by Bunkers et al. (2000), originally developed using storm data from the United States, is evaluated regarding its applicability in Central Europe, where storm environments have other dynamic and thermodynamic characteristics owing to different geographical features. As a first step, the motion of 354 observed supercells in the warm season (April to September) 2013–2016 is compared to the motion obtained with the original parameterization. The cells are classified as right-moving or left-moving supercells due to their motion direction with regard to the vertical wind shear of the environment, which is calculated using high-resolution model analyses. Afterwards, the accuracy of the parameterization is checked for both motion classes, as well as for classifications according to the lifetime, track length, and severity proxies of the cells. Clear differences between observed and parameterized motion are obtained for all categories, calling for an adjustment of the parameterization in a second step. This adjusted parameterization improves the storm motion estimation for most of the storm categories. A better storm motion estimation improves the calculation of storm-relative helicity, enabling a more reliable nowcasting and forecasting of supercell potential.